Aid to Africa : French and British policies from the Cold War to the new millennium - Cumming, Gordon (Burlington, VT : Ashgate, 2001)
"The end of the Cold War forced Western donors to rethink their aid relations with Africa. This book looks at two of these donors, France and Britain, and asks whether the development programmes of these former colonial powers have undergone radical changes since the end of the Old World Order. It focuses on the introduction of a controversial new 'regime' trend - political conditionality - and uses policy models to illustrate the driving forces behind this new development strategy and explain substantial differences in France and Britain's practice of political conditionality in Togo and Kenya. Overall, this volume - the first comparative study of French and British aid in the post Cold War period - offers fresh insights into the evolution of the political assistance agenda and into deeper forces at work within the French and UK policy processes."--Jacket.
Map of Contemporary Africa -- What is Aid? -- What is Aid for? -- Western Aid in a Cold War Context -- French and British Aid: The Cold War Record -- A Changing Agenda? -- French and UK Policy-Making: Actors and Institutions -- The Dynamics of Aid Policy-Making -- French and UK Aid Practice in Togo and Kenya -- Aid Practice: Towards a Deeper Understanding -- Conclusion: Rising to the Challenges of the new Millennium? -- France's Privileged Aid Recipients -- French Military Interventions in Black Africa -- French Non-Governmental Organisations -- French Aid Structures Before 1998 -- Organigramme of ODA -- Organigramme of French Foreign Ministry Since 1998 -- Organigramme of DfID -- French Aid Structures Since 1998.
Includes bibliographical references (pages 419-438) and index.
Keywords: 1900-1999; Economic assistance, French -- Africa; Economic assistance, British -- Africa; z; z; Africa; United Kingdom; France; foreign policy; development cooperation; Economic assistance, British; Economic assistance, French; Economic history; Economic policy; Ontwikkelingssamenwerking; Economic assistance, French -- Africa; Economic assistance, British -- Africa; France -- Economic policy -- 20th century; Great Britain -- Economic policy -- 20th century; France -- Economic conditions -- 20th century; Great Britain -- Economic conditions -- 20th century; France -- y; Grande-Bretagne -- y; France -- y; Grande-Bretagne -- y; Africa; France; Great Britain; Great Britain -- Economic conditions -- 20th century; France -- Economic policy -- 20th century; Great Britain -- Economic policy -- 20th century; France -- Economic conditions -- 20th century